Nuclear development in Brazil: a historical review (2012)
Nuclear development in Brazil reached today was the result of several factors, including the state of science and technology cooperation between the powers of the Cold War and the political will of its rulers who visualized the development of nuclear energy for peaceful purposes, as a springboard to national economic progress. This article describes, from a historical perspective, the factors that allowed Brazil to reach this level of nuclear development, as well as the obstacles it has faced against the nuclear powers, their position on the Nuclear Nonproliferation Treaty and objectives and achievements of its nuclear policy.